مفهوم الشعوب الأصلية في القانون الدولي - مستاوي, حفيظة (Revue jurisprudence; No 17 (2018): مجلة الاجتهاد القضائي, 2018)
إن الاهتمام بالشعوب الأصلية وحماية حقوقها من أهم متطلبات احترام التنوع الثقافي، من خلال استيعاب المجتمعات لحقوق الإنسان؛ وذلك بأن تفهم أن الإنسان مهما كان مختلفا عرقيا، دينيا أو لغويا فهو متساو مع الآخر حكاما ومحكومين، والجميع يبقون على مسافة واحدة من تلك الحقوق والواجبات في المجتمع. وبلا شك فإن ضبط مفهوم الشعوب الأصلية من حيث وجودها ككيان مستقل بذاته عن باقي مكونات المجتمع في خصائصه المميزة ووضعه القانوني، هو من الأولويات التي يجب التركيز عليها باعتباره الإطار الأساسي لإعمال حقوق هذه الشعوب. الكلمات المفتاحية: الشعوب الأصلية - المجموعات عرقية – حقوق الإنسان - التميز الثقافي.  Résumé: The care of indigenous peoples and protect her rights is of the most requirements  respect for cultural diversity, by absorbing the communities for human rights; and so that you understand that man no matter how different ethnically, religiously and linguistically it evenly with the other rulers and ruled alike, everyone is staying at the same distance from the rights and duties in the society. Without a doubt, Adjust the concept of indigenous peoples in terms of its existence as an entity in itself independent from the rest of the components of society in its own characteristics and legal status, it is one of the priorities that should be the focus because it is considered the basic.   Mots clés: indigenous peoples, cultural diversity, human rights.